2017
DOI: 10.5455/medarh.2017.71.89-92
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Results Classical and Eversion Carotid Endarterectomy

Abstract: Introduction:Atherosclerosis blood vessels, be it on extra-cranial or intra-cranial circulation, the most common cause of incidents such as cerebro-vascular insult (ICV). Carotid endarterectomy (CEA) is a preventive operation to reduce the risk of stroke and it can be performed by eversion carotid endarterectomy (E-CEA) or a classical carotid endarterectomy (C-CEA). The aim of this study was to investigate the influence of the used techniques in basic perioperative results and the incidence of postoperative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In studies that found ECEA and patch closure superior to the primary closure technique, no difference was reported concerning perioperative stroke (21). In light of current literature, the advantages of each surgical technique over the other is still debatable (22). There was no correlation between CCEA or ECEA techniques and stroke development in the study.…”
Section: Discussionmentioning
confidence: 75%
“…In studies that found ECEA and patch closure superior to the primary closure technique, no difference was reported concerning perioperative stroke (21). In light of current literature, the advantages of each surgical technique over the other is still debatable (22). There was no correlation between CCEA or ECEA techniques and stroke development in the study.…”
Section: Discussionmentioning
confidence: 75%
“…Five of the six studies in our review are observational studies [ [3] , [4] , [5] , [6] , [7] ] and only one is a randomized trial [ 2 ]. Two studies had a large sample size of more than 1000 patients [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“… *Group 2 CCEA: 152 (0.9) patients. *P value = 0.84 *Statistically Insignificant *Large sampled size *Non-randomized retrospective analysis of prospectively collected data *1-year follow-up for about half of the patients Djedovic M et al, 2017, Medical archives journal, Bosnia and Herzegovina [ 4 ]. Retrospective-Prospective study Level 3 *Total of 173 patients.…”
Section: Search Outcomementioning
confidence: 99%
“…The technique is associated with low restenosis rates due to the ellipsoid suture line, and the appearance of a false anastomotic aneurysm is almost impossible. 2,[7][8][9][10][11] Due to the above advantages of the eversion technique, the method appears to be progressively removed from the shadow of classical endarterectomy, although it remains not widely accepted by the vascular surgery community; this may be due to tradition and a habit in performing the standard conventional endarterectomy technique, and the subsequent insufficient imparting of the ECEA technique to younger vascular surgeons. In classical endarterectomy through the elongated arteriotomy, the fixation of the distal residual atheroma through tacking sutures and the use of shunt during carotid clamping are taught with relative ease 10) ; in ECEA, a shunt cannot be easily inserted until eversion is completed, and there may be problems in accessing the distal ICA, if a distal extension of the atheroma has been underestimated before the division of the vessel.…”
Section: Discussionmentioning
confidence: 99%